Study of Community Participation in Tourism Village Development and its Impact on Community Economy in Kebon Ayu Village, Lombok, Indonesia - Sifa’ul Jannah; Mansur Afifi; Baiq Saripta Wijimulawiani (Tinta Emas Publisher, 2023)
The development of Kebon Ayu Tourism Village is a form of community empowerment and has had a positive impact on the local community. This research uses a descriptive qualitative method with the aim of analysing the form of village community participation in the development of tourism villages and to analyse the impact of tourism village development on the economy of the community in Kebon Ayu Village, Gerung District, West Lombok Regency. The research was conducted in Kebon Ayu Village which is a tourism village that has the potential to be developed. The results showed that almost all Kebon Ayu Villagers have participated in tourism activities and have been ready in the tourism industry. The development of Kebon Ayu Tourism Village creates more economic activities for the community. The creation of new jobs, additional income for the community, and increased selling value of agricultural products.